(untitled) (Update Dental College Journal, 2019)
Background: LSTR therapy is considered as one of the most widely accepted clinical procedure for the treatment of permanent tooth with irreversible pulpitis with minimum destruction of tooth tissue Objective: To evaluate the clinical and radiographic findings of permanent tooth with irreversible pulpitis by LSTR 3Mix MP therapy and compare with conventional root canal therapy. Methods: According to inclusion and exclusion criteria, a total of 40 teeth were enrolled in this study, out of which 20 teeth treated with LSTR 3Mix MP Therapy, (Group-I) and the remaining 20 teeth treated with conventional root canal therapy (Group-2). Clinical and radiological Follow up examinations were performed at 3, 6- and 12-months interval to investigate the incidence of postoperative pain, tenderness to percussion, swelling and periodical radiolucency, collected date was analyzed by using Statistical package for Social Science (SPSS) version 17. Statistical analysis was performed by Chisquare test to assess the difference between the clinical outcome of Group 1 and 2; a value of P<0.05 was considered as statistically significant. Results: At 3 months observation period, LSTR and Conventional root canal therapy showed 100% success rate in treating teeth with irreversible pulpits; neither pain nor any tenderness on percussion or post-operative swelling was observed. Radiographic examination also revealed no sign of radiolucent area. At 6 and 12 months following the completion of the treatment, except in one case in each observation period, there results were similar to that of 3 months. One LSTR (5%) and one conventional (5%) therapy reported pain, tenderness on percussion and swelling with peripical lesion. There were no statistical differences between the two groups (p>0.05). Conclusions: It can be concluded that LSTR 3 Mix MP Therapy proved to be effective in treating teeth with irreversible pulpitis; with similar clinical and radiological outcome to conventional root canal treatment within one-year observation period. Update Dent. Coll. j: 2019; 9 (2): 20-26